“Laissez-faire under a bell jar” Marquis Childs and the Sweden-fad of the Roosevelt Era - Östlund, David (Scandinavistica Vilnensis, 2014)
For decades “Swedology” was a rich and polemically charged genre. “Swedophiles” and “Swedoclasts” were quite as eager to deploy images of Sweden as weapons in foreign contexts as they were interested in the country as such. A telling example is the genre’s early classic, Marquis W. Childs’s Sweden: The Middle Way from 1936. With the backdrop of Dwight Eisenhower’s attempt to get back at Childs by branding Sweden as an extreme society in 1960, this essay aims to see Childs’s book as an argument in its original context during the New Deal. Rather than initiating the 1930s’ American wave of Swedophilia, Childs phrased his argument as an implicit polemic against its apparent exaggerations. Sweden was not a Utopia; the point in studying its example was on the contrary the pragmatism shown in the Swedes’ attempts to solve everyday problems in a reasonable and genuinely democratic way, negotiating and compromising. As a text implicitly supporting the Roosevelt agenda, Childs’s book was far from encouraging federal dirigisme, expert rule and central planning (“social engineering”): on the contrary the message to other New Dealers was to shun such things in favor of grass-roots activities and initiatives. The predominant theme – the consumers’ cooperation movement’s central role in counteracting monopolies, thus creating economic efficiency and turning Sweden into the world’s only truly working laissez-faire economy – harmonized with Childs’s commitment to projects like the federal rural electrification program, which in a “Swedish” manner was founded on co-ops and a vision of popular self-determination.